Effect of Curcumin on Nitric Oxide and Endothelin-1 Levels in L-NAME-Induced Preeclamptic Wistar Rat - Rahardjo, Bambang; Dewi, Ratih Frastika; Wiyasa, I Wayan Arsana; Handayani, Puspita; Prasetyorini, Nugrahanti; Wibisono, Hermawan (Faculty of Medicine, Universitas Padjadjaran, 2024)
Preeclampsia is a pregnancy disorder marked by the onset of hypertension after the 20th week, posing risks such as cardiovascular disease. Curcumin, a commonly consumed herbal medicine, has been investigated as a potential antihypertensive agent in mouse models of preeclampsia. This study took place in the Bioscience Laboratory of Universitas Brawijaya from March to August 2023, employing a true experimental design with various groups of mice receiving different treatments. Nitric oxide (NO) and endothelin-1 (ET-1) levels were measured using calorimetry and ELISA. The rats were divided into five groups: positive control, negative control and P1, P2, and P3 as the treatment groups. Treatment grups received fifferent curcumin doses of 30mg/kgBW/day, 50mg/kgBW/day, and 100mg/kgBW/day for P1, P2, and P3, respectively. Data analysis using the One-Way ANOVA and Post Hoc LSD revealed that curcumin at 100mg/kgBW/day significantly increased the NO level of 47.75±22.6 and decreased the ET-1 level of 67.03±24.47 when compared to the positive control (p<0.05). However, the 30mg/kgBW/day and 50mg/kgBW/day doses did not significantly affect the NO and ET levels. In conclusion, curcumin supplementation shows positive effects on NO and ET-1 levels in L-NAME-induced preeclamptic Wistar rats, highlighting its potential as an effective intervention for managing this pregnancy-related disorder.